Revisión sistemática del efecto del ácido fosfórico usado en resinas compuestas sobre la desmineralización dentinal - María Elena Cuartas; Ana Catalina Castaño; Elizabeth Llano (Universidad de Antioquia, 2005)
In this systematic review, a meta-analysis type, the effect of phosphoric acid was evaluated on the demineralization depth of the dentinal structure, according to the application time, the concentration, the pH and the agglutinant type in four selected articles from 1.731 that were reviewed and that were published between 1990 and 2003. The global measurement of the result used, was the standard difference of average depth of dentinal demineralization produced by the acid. It was found that this depth is directly proportional to the application time of phosphoric acid. For the other variables (concentration, pH and type of agglutinant) significant conclusions could not be reached due to the few data obtained, which suggests that there is not enough scientific evidence to support this kind of procedure.